The purpose and characteristics of financial information for SME: European experience - Kovács, Levente; Poberezhny, Roman (NTU "KhPI", 2016)
Describes the purpose and features of financial information for small and medium businesses. Summarized the European experience, developed scientific and practical recommendations on its use in Ukrainian conditions.

Розглянуто цілі і характеристики фінансової інформації для малого і середнього бізнесу. Узагальнено європейський досвід, розроблено науково-практичні рекомендації по його використанню в українських умовах.
Keywords: finance; information; Ukraine`s economics; фінанси; забезпечення інформаційне; економіка України; досвід європейський